2021
DOI: 10.1016/j.psj.2020.11.074
|View full text |Cite
|
Sign up to set email alerts
|

Effects of monobutyrin supplementation on egg production, biochemical indexes, and gut microbiota of broiler breeders

Abstract: The objective of the present study was to determine the effect of monobutyrin supplementation on egg production, biochemical indexes, and gut microbiota of broiler breeders at the late stage of production. A total of 180 healthy Qingyuan partridge broilers were randomly assigned to 2 groups: 1) corn–soybean meal–based diet and 2) basal diet supplemented with 250 mg monobutyrin/kg. Each treatment group had 6 replicates/cages with 15 birds within each replicate. The experiment started at week 33 and lasted for 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The positive effect of tributyrin on egg weight and feed efficiency could be attributed to enhanced breeders’ intestinal health and improved gastrointestinal functionality. Similarly, Feng et al. (2021) also shown that supplementation of monobutyrin at 250 mg/kg level increased egg weight, but had no effect on egg production rate and feed conversion rate in broiler breeders.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The positive effect of tributyrin on egg weight and feed efficiency could be attributed to enhanced breeders’ intestinal health and improved gastrointestinal functionality. Similarly, Feng et al. (2021) also shown that supplementation of monobutyrin at 250 mg/kg level increased egg weight, but had no effect on egg production rate and feed conversion rate in broiler breeders.…”
Section: Discussionmentioning
confidence: 88%
“…It is also indicated that butyrate and its derivatives (butyric acid, sodium or calcium butyrate, and butyrate glycerides) were found to exert antioxidant effect in animals’ models in vivo or in vitro ( Lin et al., 2014 ; Wu et al., 2016 ; Memon et al., 2019 ; Guo et al., 2020 ). On the same time, lots of studies have demonstrated that sodium butyrate and butyrate glycerides (such as tributyrin and monobutyrin) could improve intestinal health and have beneficial effects on performance of broilers, laying hens and breeders ( Czerwinski, et al., 2012 ; Jahanianand Golshadi, 2015 ; Kaczmarek et al., 2016 ; Bedford et al., 2017 ; Bedford and Gong, 2018 ; Yang et al., 2018 ; Zhao et al., 2019 ; Lan et al., 2020 ; Feng et al., 2021 ). However, the response of broiler breeders with different reproduction performance to tributyrin on ovarian antioxidant capacity and function in is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…For example, botanical bioactives such as green tea and rosemary extracts are shown to promote intestinal immune system development as well as regulate antibody responses in chickens ( Rostami et al, 2018 ; Liu et al, 2021 ). Organic acids such as butyric acid and its derivatives (glycerides) can improve bird performance and modulate host immune responses ( Ebeid and Al-Homidan, 2022 ), as well as provide antimicrobial effects against enteric pathogens such as Salmonella Typhimurium and Clostridium perfringens ( Namkung et al, 2011 ; Bedford and Gong, 2018 ; Feng et al, 2021 ; Xiao et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Maintaining a healthy level of intestinal development is essential to ensuring animals’ health and growth performance [ 14 ]. A variety of microorganisms reside in the chicken digestive tract, forming symbiotic relationships that affect nutrition, metabolism and immunity [ 15 ].…”
Section: Introductionmentioning
confidence: 99%